2009
DOI: 10.1017/s1744137409001295
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and US regional development: a study of Massachusetts and Virginia

Abstract: The development of the American economy was accompanied by significant spatial income inequalities between the northern and southern regions. While many factors contributed to northern industrialization and southern stagnation, an important factor was differences in the region's institutions. In the North, a democratic institution fostered growth whereas in the South, oligarchic institutions favored status quo. To gain insights on the nature and causes of this divergence, this paper examines the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…So far, despite the great effort to address the issue of the impact of institutional quality on the growth rate (see, for an updated survey, Valeriani and Peluso ), there are negligible analyses carried out at a regional level, as argued by Charron and Lapuente (). Within this tiny stream of literature we may quote Kim () who conducted a comparative analysis between Massachusetts and Virginia, finding evidence that the difference between these two North American states in terms of political economy and institutional quality may explain the unequal income distribution. Degirmenci (), in an empirical analysis performed on Turkey, demonstrated that although the sub‐national institutions are substantially the same countrywide, their density and quality varies from one area to another, and this has an impact on regional growth and development.…”
Section: Literature Survey and Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, despite the great effort to address the issue of the impact of institutional quality on the growth rate (see, for an updated survey, Valeriani and Peluso ), there are negligible analyses carried out at a regional level, as argued by Charron and Lapuente (). Within this tiny stream of literature we may quote Kim () who conducted a comparative analysis between Massachusetts and Virginia, finding evidence that the difference between these two North American states in terms of political economy and institutional quality may explain the unequal income distribution. Degirmenci (), in an empirical analysis performed on Turkey, demonstrated that although the sub‐national institutions are substantially the same countrywide, their density and quality varies from one area to another, and this has an impact on regional growth and development.…”
Section: Literature Survey and Methodological Issuesmentioning
confidence: 99%
“…The duration of civil disputes is a measure of the time necessary for private enforcement of the law (Silbey and Sarat ; Djankov et al ; Kim ), and is a good indicator of institutional quality because, as recently affirmed by the World Bank, ‘justice delayed is justice denied’ (World Bank ).…”
Section: The Institutional Framework and Its Implications For Theory mentioning
confidence: 99%
“…This weakens the main mechanism of the model as uncertainty about the distribution of the costs of uprisings falls. Moreover there were important institutional differences between the south, with oligarchic institutions, and the north, with more democratic institutions (Kim, 2009).…”
Section: The Americas After Independencementioning
confidence: 99%
“…Institutional factors also could lead to increase in income inequality as Holcombe and Boudreaux (2016) concluded in their study on market institutions. Kim (2017) assigned divergence in legal and political institutions in explaining differences in the level of economic development in Virginia and Massachusetts in the USA.…”
Section: Literature Reviewmentioning
confidence: 99%